Pacing patterns in biathlon sprints - Losnegard, T. (Journal of Biathlon Coaching, 2024)
The importance of assessing and modifying pacing patterns for biathletes has recently been discussed by Losnegard et al. in their study, `Highly Trained Biathletes With a Fast-Start Pacing Pattern Improve Time-Trial Skiing Performance by Pacing More Evenly,` published in the International Journal of Sports Physiology and Performance. The study exposes the significance of adopting a consistent lap-to-lap approach for fast-starting biathletes, offering valuable insights for coaches. The project received support from the IBU Research Grant Programme 22/23.